Analysis of Consumers’ Perception at the Food Court of Lampung Walk by Using Multidimensional Scaling Approach - Andriani, Siska; Rakhmawati M, Rosida; Pratiwi, Dona Dinda; Ariawan, Feri; Murtianto, Yanuar Hery; Yustinaningrum, Bettri (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
This research aims to determine customer perceptions of food outlets located on Lampung Walk and to find out the similarities between food outlets on Lampung Walk using Multidimensional Scaling analysis. The methods used in this reseach are descriptive method and analytic survey using inferential statistics. The research places are the food outlet of Kedai Urang, el’s coffee, dimsum moresto, pondok hijau and sup duren ewok. The results of this research known that the highest customer perceptions is in Kedai Urang with affordable price attributes, more portions, good taste, neat and clean presentation. So that for other business developers can pay attention to the attributes of consumer perception for business continuity.